MicroRNA let-7f-5p regulates PI3K/AKT/COX2 signaling pathway in bacteria-induced pulmonary fibrosis via targeting of PIK3CA in forest musk deer - Wei Zhao; Jianguo Cheng; Yan Luo; Wenlong Fu; Lei Zhou; Xiang Wang; Yin Wang; Zexiao Yang; Xueping Yao; Meishen Ren; Zhijun Zhong; Xi Wu; et al. (PeerJ, 2022)
Background Recent studies have characterized that microRNA (miRNA) is a suitable candidate for the study of bleomycin/LPS-induced pulmonary fibrosis, but the knowledge on miRNA in bacteria-induced pulmonary fibrosis (BIPF) is limited. Forest musk deer (Moschus berezovskii, FMD) is an important endangered species that has been seriously affected by BIPF. We sought to determine whether miRNA exist that modulates the pathogenesis of BIPF in FMD. Methods High-throughput sequencing and RT-qPCR were used to determine the differentially expressed miRNAs (DEmiRNAs) in the blood of BIPF FMD. The DEmiRNAs were further detected in the blood and lung of BIPF model rat by RT-qPCR, and the targeting relationship between candidate miRNA and its potential target gene was verified by dual-luciferase reporter activity assay. Furthermore, the function of the candidate miRNA was verified in the FMD lung fibroblast cells (FMD-C1). Results Here we found that five dead FMD were suffered from BIPF, and six circulating miRNAs (miR-30g, let-7f-5p, miR-27-3p, miR-25-3p, miR-9-5p and miR-652) were differentially expressed in the blood of the BIPF FMD. Of these, let-7f-5p showed reproducibly lower level in the blood and lung of the BIPF model rat, and the expression levels of PI3K/AKT/COX2 signaling pathway genes (PIK3CA, PDK1, Akt1, IKBKA, NF-κB1 and COX2) were increased in the lung of BIPF model rats, suggesting that there is a potential correlation between BIPF and the PI3K/AKT/COX2 signaling pathway. Notably, using bioinformatic prediction and experimental verification, we demonstrated that let-7f-5p is conserved across mammals, and the seed sequence of let-7f-5p displays perfect complementarity with the 3’ UTR of PIK3CA gene and the expression of the PIK3CA gene was regulated by let-7f-5p. In order to determine the regulatory relationship between let-7f-5p and the PI3K/AKT/COX2 signaling pathway in FMD, we successfully cultured FMD-C1, and found that let-7f-5p could act as a negative regulator for the PI3K/Akt/COX2 signaling pathway in FMD-C1. Collectively, this study not only provided a study strategy for non-invasive research in pulmonary disease in rare animals, but also laid a foundation for further research in BIPF.